2020
DOI: 10.31234/osf.io/364qj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are people excessively pessimistic about the risk of coronavirus infection?

Abstract: The recent emergence of the SARS-CoV-2 in China has raised the spectre of a novel, potentially catastrophic pandemic in both scientific and lay communities throughout the world. In this particular context, people have been accused of being excessively pessimistic regarding the future consequences of this emerging health threat. However, consistent with previous research in social psychology, a large survey conducted in Europe in the early stage of the COVID-19 epidemic shows that the majority of respondents wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 8 publications
5
49
0
10
Order By: Relevance
“…We can speculate that reframing the emergency within a national dimension can amplify the perceived susceptibility of individuals [ 92 , 93 ] and thus increase the adoption of behavioral changes [ 4 , 94 ]. Indeed, previous studies showed that at the beginning of February 2020, people were overly optimistic regarding the risks associated with the new virus circulating in Asia, and their perception sharply changed after the first cases were confirmed in their countries [ 9 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can speculate that reframing the emergency within a national dimension can amplify the perceived susceptibility of individuals [ 92 , 93 ] and thus increase the adoption of behavioral changes [ 4 , 94 ]. Indeed, previous studies showed that at the beginning of February 2020, people were overly optimistic regarding the risks associated with the new virus circulating in Asia, and their perception sharply changed after the first cases were confirmed in their countries [ 9 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of surveys conducted in late February provide a glimpse of the possible effects of these approaches. These surveys report that citizens of several European countries, despite the grim news coming from Asia, were overly optimistic about the health emergency, placing their risk of infection at 1% or less [ 9 ]. As in 1918, countries that reacted earlier rather than later were better able to control the virus, with significantly fewer infections [ 10 - 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This claim is supported by Zettler, Schild, Lilleholt, & Böhm (2020), who reported that the HEXACO personality domain of emotionality (characterized by exaggerated levels of anxiety, fear, and emotional reactivity) was associated with a greater level of acceptance of government-mandated personal restrictions. Further, Kuper-Smith, Doppelhofer, Oganian, Rosenblau, and Korn (2020) found that community members in the USA, UK, and Germany consistently underestimated their likelihood of both becoming infected and transmitting COVID-19 in comparison to estimates about the 'average' member of the public (see also Raude et al, 2020). They also reported negative correlations between self-perceived likelihood of infecting others and engaging in hygiene-related behaviors (e.g., hand washing and social distancing), suggesting that increasing fears about contracting the virus might lead to less risky social behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…This claim is supported by Zettler et al (2020), who reported that the HEXACO personality domain of emotionality (characterized by exaggerated levels of anxiety, fear, and emotional reactivity) was associated with a greater level of acceptance of government-mandated personal restrictions. Further, Kuper-Smith et al (2020) found that community members in the USA, the UK, and Germany consistently underestimated their likelihood of both becoming infected and transmitting COVID-19 in comparison with estimates about the "average" member of the public (see also Raude et al 2020). They also reported negative correlations between self-perceived likelihood of infecting others and engaging in hygiene-related behaviors (e.g., hand washing and social distancing), suggesting that increasing fears about contracting the virus might lead to less risky social behaviors.…”
mentioning
confidence: 99%